Household heterogeneity, aggregation, and the distributional impacts of environmental taxes - Sebastian Rausch; Giacomo Schwarz (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
This paper examines how the general equilibrium incidence of an environmental tax depends on the effect of different incomes and preferences of heterogeneous households on aggregate outcomes. We develop a Harberger-type model with general forms of preferences and substitution between capital, labor, and pollution in production that captures the impact of household heterogeneity and interactions with production characteristics on the general equilibrium. We theoretically show that failing to incorporate household heterogeneity can qualitatively affect incidence. We quantitatively illustrate that this aggregation bias can be important for assessing the incidence of a carbon tax, mainly by affecting the returns to factors of production. Our findings are robust to a number of extensions including alternative revenue recycling schemes, preexisting taxes, non-separable utility in pollution, labor-leisure choice, and multiple commodities.
Keywords: H23; Q52; 330; Ökosteuer; Verteilungswirkung; Wohlfahrtsanalyse; Privater Haushalt; Allgemeines Gleichgewicht; USA